Industrialización de granos andinos (carneamarant y hojuamarant) - Cruz Naula, Irene Paola (2016)
At this investigation job with the topic "Industralization of andean grains" (Carneamarant and hojuemarant) where there were obtained two products of amaranth (amaranthus caudatus L) (vegetable leaflets), with the objective to get the cultives of small producers of grains, specially the amaranth, aditionally presenting it to the society as a new consumption alternative, its nutritional value and to take advantage of the amaranth. After production a tasting was made over teachers and students of Agroindustry career showing its acceptability. With the obtained information it was concluded that the elaborated products take ranges of 80 % of acceptance for the panel of tasting. Therefore the formulations established respectively are: vegetable meat of amaranth (70 % amaranth + 15 % integral flour of wheat + 5 % starch of soy bean + 7 vegetable % + 0.5 % saborizante to meat + 0.9 % go out + 1.6 % spices.) and leaflets of amaranth (70 % amaranth + 20 % integral flour of wheat + 5 % starch of soy + 5 % honey of bee + 3 % spice. + 1.5 % of saccharose + 0.5 % impalpable sugar).